Soil Microbial Properties of Durum Grown after Camelina, Carinata, Cover Crops, and Fallow - Sadikshya R. Dangi; Brett L. Allen; Jay D. Jabro; Tatyana A. Rand; Joshua W. Campbell; Rosalie B. Calderon (Agronomy)
Novel crop rotation is an important factor influencing the composition of soil microorganisms. However, the effect of introducing oilseed and cover crops (CCs) into monoculture durum rotations on soil microbial communities is not clear in the Northern Great Plains. The objective of this study was to evaluate the effects of 2-year durum (Triticum durum D.) rotations with Ethiopian mustard (Brassica carinata A.) or camelina (Camelina sativa L.) or a 10-species forage/CC mix planted to replace fallow rotations with wheat on soil microorganisms. This study was designed as a randomized complete block with three replications in a no-tillage system. The results showed that total bacterial proportion was significantly higher in durum following fallow and camelina compared to durum following CC and carinata. Total fungal proportion was significantly higher in durum following CC compared to durum following oilseed crops and fallow. The fungal-to-bacterial ratio was significantly higher in durum following CC compared to durum following camelina and fallow. The crop species, soil pH and highly variable rainfall influenced the microbial community dynamics. The abundance of specific microbial groups due to crop-related changes might play a key role in the yield of subsequent crops and soil biological health. This study provides valuable insights into the use of CC mix and oilseeds as an alternative crop for fallow in a wheat–fallow system under dryland farming conditions. Future work is required to elucidate the biological mechanisms and functions of the soil microbial communities in the preceding and subsequent crop relative to soil health and crop productivity.